Comparison of the results of regional chemotherapy alone and in combination with conform radiotherapy in patients with curable pancreatic head cancer and high surgical risk - Alexey V. Kozlov; Julia N. Vinogradova; Pavel G. Tarazov; Denis S. Kolesnikov; Luisa I. Korytova; Sergey A. Popov; Anastasiya S. Butrimova; Dmitrii A. Granov (Alʹmanah Kliničeskoj Mediciny)
Rationale: Curative surgery with subsequent adjuvant chemotherapy is the main combination treatment for pancreatic cancer (PC). However, there is the group of patients with resectable tumors who cannot be resected due to severe comorbidities and as such are subjects for palliative anti-tumor treatment.